Taming the Beloved Beast : How Medical Technology Costs Are Destroying Our Health Care System - Callahan, Daniel, 1930-2019 (Book collections on Project MUSE., 2009)
Technological innovation is deeply woven into the fabric of American culture, and is no less a basic feature of American health care. Medical technology saves lives and relieves suffering, and is enormously popular with the public, profitable for doctors, and a source of great wealth for industry. Yet its costs are rising at a dangerously unsustainable rate. The control of technology costs poses a terrible ethical and policy dilemma. How can we deny people what they may need to live and flourish? Yet is it not also harmful to let rising costs strangle our health care system, eventually harming.